Without a Trace... : Pogrom, Sweatshop, Gulag: The Jewish Radical Odyssey of Noah and Miril London - Holmes, John D. (Historical Materialism Book Series, 2026)
This biography gives an inside story of US and Soviet Communism, their similarities and parallels, and the Soviet bureaucracy in the Stalin era. Unprecedented research in Yiddish-language Jewish archives and underresearched Soviet archives enable genuine revelations. This book tells you how revolution in Russia, twentieth-century Jewish history, US and Russian labor history and the evolution of Stalinism are intertwined threads. They link historical moments on both sides of the Atlantic Ocean and around the world. The London story has much to say about the present day world and prospects for the future. The tragic odyssey of the Londons gives insight into the nature and origins of Stalinism and the causes of the "Great Terror," the most mysterious episode of Soviet history. And Noah London's career as a leader of the Stalinist industrial revolution in the Donbass who became a secret dissident due to the Ukrainian famine sheds vital light on today's war-torn Donbass.